Low-dimensional modeling of non-isothermal twin-jet flow - Gunes, H. (Elsevier BV, 2002)
Abstract The two-dimensional incompressible non-isothermal confined twin-jet flow has been numerically studied in the transitional flow regime by a finite volume technique. The proper orthogonal decomposition (POD) is applied to the instantaneous flow and temperature data to obtain POD-based basis functions for both velocity and temperature fields. The low-dimensional Galerkin models of the full Navier-Stokes and energy equations are constructed by the Galerkin projection onto basis functions. The numerical implications, the validity of the models and their performance characteristics are discussed.